Eye injuries in typhus - Mackehenie, Daniel (1938)
Even though they are relatively incomplete our observations on this subject due to the scarcity of pathological material and the condition in which it came to his studio, a description deemed advisable to encourage other observers to complete our anatomical chart. Another reason that Simpele not publish these notes is to compare results with those of nunestros several researchers and notice their similarities.